Water extract of brewers rice induces antiproliferation of human colorectal cancer (HT-29) cell lines via the induction of apoptosis - Bee, Ling Tan; Mohd Esa, Norhaizan; Karim, Roselina (Verduci Editore srl, 2015)
OBJECTIVE: Brewers' rice, a mixture of broken rice, rice bran, and rice germ, is a rice by-product in the rice industry. The present study was designed to investigate the in vitro cytotoxicity of the water extract of brewers' rice (WBR) against colorectal cancer (HT-29) cells.